2012
DOI: 10.1103/physrevlett.108.197201
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Proximity Effect inYBa2Cu3O7/La2/3Ca1/

Abstract: Using neutron reflectometry and resonant x-ray techniques we studied the magnetic proximity effect (MPE) in superlattices composed of superconducting YBa2Cu3O7 and ferromagnetic-metallic La0.67Ca0.33MnO3 or ferromagnetic-insulating LaMnO(3+δ). We find that the MPE strongly depends on the electronic state of the manganite layers, being pronounced for the ferromagnetic-metallic La0.67Ca0.33MnO3 and almost absent for ferromagnetic-insulating LaMnO(3+δ). We also detail the change of the magnetic depth profile due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 27 publications
4
81
2
Order By: Relevance
“…31, this decrease is even anomalously enhanced below the superconducting transition temperature. Additional evidence for an intrinsic electronic origin of the depleted layers in the YBCO/LCMO SL comes from the observation that the magnetic proximity effect and thus these depleted layers are absent for a corresponding YBCO/LaMnO 3+δ SL for which the manganite layers are insulating 31 . The large FM moments of the Mn ions persist here right up to the interface.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…31, this decrease is even anomalously enhanced below the superconducting transition temperature. Additional evidence for an intrinsic electronic origin of the depleted layers in the YBCO/LCMO SL comes from the observation that the magnetic proximity effect and thus these depleted layers are absent for a corresponding YBCO/LaMnO 3+δ SL for which the manganite layers are insulating 31 . The large FM moments of the Mn ions persist here right up to the interface.…”
Section: Resultsmentioning
confidence: 92%
“…Hoffmann et al reported an enhancement in the Mn 3d occupation next to the interface and concluded that their PNR data support the dead layer model 27 . On the other hand, Chakhalian et al reported x-ray magnetic circular dichroism (XMCD) data which established the presence of a ferromagnetic Cu moment and thus were interpreted in terms of the "inverse proximity effect model" 28 31 . On this SL they performed a combination of PNR, XMCD and x-ray resonant magnetic reflectometry (XRMR) which showed that the magnetic proximity effect at the YBCO/LCMO interface involves in fact both effects, i.e.…”
mentioning
confidence: 99%
“…Later, however, PME was observed in conventional superconductors, like Al or Nb, which required a less exotic explanation (see review [1] on the PME in bulk superconductors). One of such explanations is based on flux trapping below T C with further compression upon cooling [2,3].A similar effect, the increase of magnetic moment, was also observed recently in superconductor/ ferromagnet heterostructures (S/F) of different compositions [4][5][6][7][8][9][10] with both HTSC and conventional superconductors. For the explanation of the PME in S/F structures different models based on electrodynamical or exchange coupling mechanisms were proposed.…”
mentioning
confidence: 80%
“…Various x-ray and neutron techniques have been used to study bilayer/trilayer/superlattice HTSC-manganite heterostructures, such as YBCO/LCMO (La 1−x Ca x MnO 3 ) and YBCO/LSMO. [15][16][17][18][19] These studies reveal (a) a strongly (but not totally) suppressed Mn ferromagnetic moment at the manganite side of the interface, and/or (b) a small ferromagnetic Cu moment developing on the HTSC side of the interface. This is consistent with the observation of a reduced saturation magnetization per manganite layer compared to the bulk value.…”
Section: Introductionmentioning
confidence: 98%